Electrochemiluminescent Arrays for Cytochrome P450-Activated Genotoxicity Screening. DNA Damage from Benzo[a]pyrene Metabolites - Hvastkovs, Eli G. (2007)
Arrays suitable for genotoxicity screening are reported that generate metabolites from cytochrome P450 enzymes (CYPs) in thin-film spots. Array spots containing DNA, various human cyt P450s, and electrochemiluminescence (ECL) generating metallopolymer [Ru(bpy)(2)PVP(10)](2+) were exposed to H(2)O(2) to activate the enzymes. ECL from all spots was visualized simultaneously using a CCD camera. Using benzo[a]pyrene as a test substrate, enzyme activity for producing DNA damage in the arrays was found in the order CYP1B1 > CYP1A2 > CYP1A1 > CYP2E1 > myoglobin, the same as the order of their metabolic activity. Thus, these arrays estimate the relative propensity of different enzymes to produce genotoxic metabolites. This is the first demonstration of ECL arrays for high-throughput in vitro genotoxicity screening.